Stimulating Neoblast-Like Cell Proliferation in Juvenile Fasciola hepatica Supports Growth and Progression towards the Adult Phenotype In Vitro - McCusker, Paul; McVeigh, Paul; Rathinasamy, Vignesh; Toet, Hayley; McCammick, Erin; O’Connor, Anna; Marks, Nikki J.; Mousley, Angela; Brennan, Gerard P.; Halton, David W.; Spithill, Terry W.; Maule, Aaron G. (PLOS Neglected Tropical Diseases, 2016)
Author Summary Parasitic worms require a host organism in order to survive and reproduce. As such, it is difficult to study them outside of a host. Some parasites can be maintained in vitro using cell culture methods; in the case of F. hepatica, previously-reported methods are unsatisfactory because they are difficult to reproduce and unable to support long term growth and development. Here we have developed a new set of methods for maintaining F. hepatica juveniles in vitro. These methods use simple, commonly available reagents and techniques, enabling us to keep fluke alive in vitro for at least 6 months, as well as stimulating the development of characteristics that resemble adult parasites. Over time, our in vitro fluke show changes in the structure and complexity of individual tissues, and the proteins they produce, such that they are more reminiscent of adult, than juvenile fluke. Additionally, we demonstrate that fluke growth is supported by the division of cells resembling stem cells, which have not been reported previously for F. hepatica. This work will support the study of liver fluke, enabling the development of new drugs and vaccines for the treatment of liver fluke infections of humans and animals.